Rancang Bangun Sistem Kontrol Beban dan Akuisisi Data Berbasis Web dengan menggunakan Single Board Computer - Irfan Firnandi; Jaja Kustija; Bambang Trisno (ELECTRANS, 2016)
Load control and data acquisition in this research designed to be accessible with web page interface. The working of data acquisition is reading analog data from voltage and current by using Adaptor and current sensor ACS712 which is then processed by Arduino and will show in web page with SBC Raspberry Pi, the web page will showing real time chart from voltage, current and apparent power, and the workings of the control system is direct control SBC Raspberry Pi pin with interface web which then will turn on relay which has connected with the electricity load. The system which researched using WiFi USB or LAN cable for connected to intranet network that cause address of web page can be access by other devices connected to the intranet network.